Strategi Pihak Sekolah Dalam Menerapkan Pembelajaran Tatap Muka Terbatas Di SMPN 1 Pangkalan Kerinci TA2021/2022 - Sri Rahayu; Wibi Wijaya; Wulan Dari (Jurnal Pendidikan dan Pembelajaran, 2022)
This research is motivated by the school's strategy in implementing limited face-to-face learning at SMP Negeri 1 Pangkalan Kerinci in the 2021/2022 academic year, Pangkalan Kerinci District, Pelalawan Regency, Riau Province. from the beginning students did the online learning process but switched to face-to-face limited. This requires schools to develop strategies in the limited face-to-face teaching and learning process (Offline) by implementing Health protocols and achieving learning objectives. The aim is to find out the school's strategy in implementing limited face-to-face learning at SMP Negeri 1 Pangkalan Kerinci for the 2021/2022 academic year. The theory in this research is Structural Functional Theory by Talcot Parson with four AGIL schemes. The research approach used is qualitative with descriptive type. Purposive sampling of research informants. Data collection techniques in the form of observation, interviews, and document studies. The unit of analysis in this study is the group. Data analysis using Miles and Huberman models. The results include: a) preparation for implementation b) vaccination implementation, c) parent/guardian approval letter, d) blended learning, e) offline and online learning implementation, f) assessment system, g) health protocol, h) understanding the material offline and online learning.